2016
DOI: 10.1159/000453033
|View full text |Cite
|
Sign up to set email alerts
|

Diesel Exhaust Particles Enhance <b><i>MUC4</i></b> Expression in NCI-H292 Cells and Nasal Epithelial Cells via the p38/CREB Pathway

Abstract: Background: Diesel exhaust particles (DEPs), the major contributors to air pollution, induce inflammatory responses in the nasal epithelium. Overproduction of airway mucins is an important pathogenic finding in inflammatory airway diseases. Objective: The aims of the present study were to determine the effect of DEPs on the expression of the mucin gene MUC4 and to investigate the underlying mechanism of DEP-induced MUC4 expression in NCI-H292 cells and primary nasal epithelial cells (PNECs). Methods: NCI-H292 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Diesel exhaust particles (DEPs), the major contributors to air pollution, significantly increased the expression of MUC4. MUC4 expression was inhibited by pre-treatment with p38 MAPK and CREB inhibitors in NCI-H292 (ATCC ® CRL-1848 TM ) and primary nasal epithelial cells stimulated with DEPs [89].…”
Section: Mucin Production and Mapk Signallingmentioning
confidence: 99%
“…Diesel exhaust particles (DEPs), the major contributors to air pollution, significantly increased the expression of MUC4. MUC4 expression was inhibited by pre-treatment with p38 MAPK and CREB inhibitors in NCI-H292 (ATCC ® CRL-1848 TM ) and primary nasal epithelial cells stimulated with DEPs [89].…”
Section: Mucin Production and Mapk Signallingmentioning
confidence: 99%
“…Our results showed that L. paracasei MG4272, MG4577, L. gasseri MG4247, and S. thermophilus MG5140 inhibited the mRNA expression of MUC4, MUC5AC, and MUC5B, which are mucin-producing genes, in NCI-H292 cells treated with DPM. Phosphorylation of CREB by p-ERK1/2 and/or p-p38 MAPK is a major intracellular mechanism for the expression of MUC4, MUC5AC, and MUC5B genes [8,34]. It has been reported that DPM-induced mucin production is mainly mediated by ERK and p38 MAPK [8].…”
Section: Discussionmentioning
confidence: 99%